Technology adaptation and digital innovation as key to management success and business competitiveness in the modern era - Syaukani, Arham; Okviar Egano Napitupulu, Dea (Lembaga Riset, Publikasi dan Konsultasi JONHARIONO, 2024)
In the modern business landscape, technology adaptation and digital innovation are critical drivers of management success and competitive advantage. This study explores the strategic adoption of digital technologies, the challenges associated with digital transformation, and their impact on business performance. The findings indicate that a gradual digitalization approach, collaboration with technology providers, and the utilization of Big Data significantly enhance operational efficiency and decision-making processes. However, organizations face challenges such as resistance to change, budget constraints, skill gaps, and cybersecurity risks, which require strategic solutions including continuous training, phased investment, workforce upskilling, and robust cybersecurity policies. Additionally, digitalization reshapes consumer behavior and industry dynamics, with increasing demand for fast, personalized, and digital-driven experiences. Companies that adopt omnichannel strategies and integrate advanced technologies are better positioned to sustain competitiveness in an evolving market. This study underscores that successful digital transformation depends on technological adoption, organizational readiness, leadership commitment, and structured implementation strategies. Businesses that embrace digital innovation effectively will achieve sustainable growth and long-term success in the digital era.